The Positive Accounting Theory Model and CEO Narcissism to Detect Earnings Management Practices of Public Companies in Indonesia - Anasta, Lawe; Oktris, Lin (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Objectives: This study wants to test the effect of the positive accounting theory model, namely leverage, profitability, and company size to detect earnings management practices in public companies in Indonesia. In addition, this study also wants to know about the effect of CEO narcissism on the practice of earnings management in public companies. Methods: This study uses secondary data from public companies in Indonesia from 2018 to 2023. Data analysis was carried out using the MRA model. Results: The results of this study indicate that the positive accounting theory model, namely leverage, profitability, and company size, has a positive effect on the occurrence of earnings management practices in public companies. In addition, the narcissistic nature of the CEO is also known to moderate the influence of leverage and company profitability in determining the occurrence of earnings management practices.